2021
DOI: 10.1055/s-0040-1719113
|View full text |Cite
|
Sign up to set email alerts
|

Do Hernias Contribute to Increased Severity of Aneurysmal Disease among Abdominal Aortic Aneurysm Patients?

Abstract: Background Connective tissue disorders could contribute to the pathogenesis of both abdominal aortic aneurysms (AAA) and hernias. We tested the hypothesis that hernias in AAA patients contribute to increased severity of the aneurysmal disease. Methods A questionnaire was used to collect information from 195 AAA patients divided into four groups: (1) survivors (n = 22) of ruptured AAA, (2) patients (n = 90) after elective open repair, (3) patients (n = 43) after elective endovascular repair (EVAR), an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Previous study by Cannon and colleagues in 1984 suggested a possible link between inguinal hernia and aortic aneurysm, which was then supported by many others [7,[24][25][26]. However, the results of conventional observational studies have been inconsistent.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous study by Cannon and colleagues in 1984 suggested a possible link between inguinal hernia and aortic aneurysm, which was then supported by many others [7,[24][25][26]. However, the results of conventional observational studies have been inconsistent.…”
Section: Discussionmentioning
confidence: 96%
“…Findings reveal that collagen levels are significantly lower in transversalis fascia samples derived from patients with inguinal hernia compared to controls. And the ratio of MMP to TIMP expression is higher in both inguinal hernia and AA, leading to ECM breakdown [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…2,7,10,20 There are a few studies in the literature that compare the groups in terms of IH development between AAA and AOD, and it has been reported that the AAA group has a greater IH rate, up to a median of 5-fold increased risk. 7,8,21 In a study comparing AAA and AOD repair, a BMI of 25 kg/m 2 or higher was found to be an independent risk factor for IH. 10 Obesity is associated with a higher intraabdominal pressure and wound-healing complications as a consequence of decreased vascularity of adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for IH are advanced age, male gender, BMI ≥ 27 kg/m 2 , diabetes, chronic obstructive pulmonary disease, chronic kidney disease, immunosuppression, use of corticosteroids, anemia, uremia, malnutrition, collagen-related diseases, smoking, neoplasia, surgical-site infection, abdominal aortic aneurysm, and emergency surgery. 8 16 17 18 19 Patients with abdominal aortic aneurysm and obese individuals are of especially high risk for IH development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation